알코올사용장애자의 음주관련 문제 분석을 위한 구조모형 - 손희정; Hee Jung Son; 이원기; Won Kee Lee; 박영신; Young Shin Park; 홍해숙; Hae Sook Hong (보건정보통계학회지, 2017)
Objectives: This study was designed to construct and test the structural equation model for the alcohol-related problem of alcohol use disorders. Methods: Data were collected by structured self-questionnaires from 229 male subjects who received >8 (greater than 8) score on Alcohol Use Disorder Identification Test (AUDIT). The Data were analyzed by SPSS 21.0 and AMOS 21.0. Results: The model fit indices for the modified hypothetical model showed Q=2.50, GFI=0.90, and CFI=0.94. As a result, Life position, parent`s drinking problem, and alcohol expectancy had significantly direct effect on alcohol-related problem. Alcohol expectancy also had mediator effect between life position and alcohol-related problem. Conclusions: Consequently, the more positive life position, the less alcohol-related problem occurred. It is necessary to change their life position, which is individual factor, to prevent or reduce the alcohol related problem of alcohol use disorders.